The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1161/01.hyp.34.6.1202
|View full text |Cite
|
Sign up to set email alerts
|

Impeded Alveolar-Capillary Gas Transfer With Saline Infusion in Heart Failure

Abstract: Abstract-The microvascular pulmonary endothelium barrier is critical in preventing interstitial fluid overflow and deterioration in gas diffusion. The role of endothelium in transporting small solutes in pathological conditions, such as congestive heart failure (CHF), has not been studied. Monitoring of pulmonary gas transfer during saline infusion in CHF was used to probe this issue. Carbon monoxide diffusion (DL CO ), its membrane diffusion (D M ) and capillary blood volume (V C ) subcomponents, and mean rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…In a study performed in post-MI patients with normal LV systolic function, an infusion of ~800 mL of saline reduced Dm by 13% 49 . In patients with mild to severe HF, a 150 ml infusion of saline produced a significant Dm reduction equivalent to 750 ml saline, whereas a 750 mL infusion of isotonic glucose solution did not decrease DLco and Dm 50 . None of these infusions caused changes in right atrial or pulmonary wedge pressures.…”
mentioning
confidence: 84%
“…In a study performed in post-MI patients with normal LV systolic function, an infusion of ~800 mL of saline reduced Dm by 13% 49 . In patients with mild to severe HF, a 150 ml infusion of saline produced a significant Dm reduction equivalent to 750 ml saline, whereas a 750 mL infusion of isotonic glucose solution did not decrease DLco and Dm 50 . None of these infusions caused changes in right atrial or pulmonary wedge pressures.…”
mentioning
confidence: 84%
“…Indeed, in heart failure patients, a low SaO 2 at rest or after alveolar-capillary membrane challenge such as fluid overload or exercise is an unusual event [71][72][73]. In healthy subjects, rapid infusion of saline is associated to a slight reduction of spirometric parameters but an unchanged DLCO and SaO 2 [74,75].…”
Section: Alveolar-capillary Membrane Dysfunctionmentioning
confidence: 99%
“…The DLCO reduction is greater when a β1-β2 blocker (carvedilol) is used compared with a β1 selective blocker (bisoprolol) (figure 5) [74]. In contrast, heart failure patients show a decrease in DLCO with even a small amount of saline infusion or physical exercise [71][72][73], suggesting that the lung fluid balance is in a critical condition. Indeed, in heart failure the alveolar-capillary membrane undergoes an extensive remodelling process.…”
Section: Alveolar-capillary Membrane Dysfunctionmentioning
confidence: 99%
“…Notably, Guazzi et al also showed that impediment of gas transfer with salt infusion in CHF, despite an increase in capillary blood volume and no variations in pulmonary hydrostatic forces, indicates an upregulation in sodium transport from blood to interstitium with interstitial edema. Redistribution of blood from the lungs, facilitating interstitial fluid reabsorption, or sodium uptake from the alveolar lumen by the sodium-glucose cotransport system might underlie the improved alveolar-capillary conductance with glucose [11,12]. In patients with chronic CHF, there is an increase in the number of alveolar type II cells [13].…”
Section: Histological Changes In Lungs With Heart Failurementioning
confidence: 99%